2022
DOI: 10.3389/fnut.2022.846974
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Coevolution of Genetics Rather Than Diet With Enterotype in Pigs

Abstract: Based on the characteristic of low diarrhea in native Chinese breeds, we introduce the enterotype model for piglets, which is a new perspective to decipher the colonization and the transition of the gut microbiota among various pig breeds. After eliminating environmental influences represented by diet, the microbiota, mainly shaped by host genetics, is focused. Three representative enterotype clusters were identified, which were represented by Bacteroides, Streptococcus, and Lactobacillus. Chinese native breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…20 The gut microbiota plays a crucial role in enhancing the gut health and performance of pigs, 41 which is involved in nutrient digestion and absorption, regulation of the intestinal immune system, 42 and protection from infection by pathogens. 43 However, due to the immature gut microbiota of weaned pigs, weaning stress could readily disturb the dynamic balance of the gut microbiota. 44 In the present study, no significant difference was observed in the alpha diversity of the microbial community in the fecal samples of piglets between the two treatments, indicating that the diversity, richness, and evenness of the bacterial community were not affected significantly by W. anomalus 13611, which is in accordance with the previous study.…”
Section: Paper Food and Functionmentioning
confidence: 99%
“…20 The gut microbiota plays a crucial role in enhancing the gut health and performance of pigs, 41 which is involved in nutrient digestion and absorption, regulation of the intestinal immune system, 42 and protection from infection by pathogens. 43 However, due to the immature gut microbiota of weaned pigs, weaning stress could readily disturb the dynamic balance of the gut microbiota. 44 In the present study, no significant difference was observed in the alpha diversity of the microbial community in the fecal samples of piglets between the two treatments, indicating that the diversity, richness, and evenness of the bacterial community were not affected significantly by W. anomalus 13611, which is in accordance with the previous study.…”
Section: Paper Food and Functionmentioning
confidence: 99%
“…Enterotyping, a method first described in human microbiome research ( Arumugam et al, 2011 ) and later applied to several pig studies, simplifies the complexity of microbiota data by creating distinct clusters within the gut microbiota ( Costea et al, 2018 ). In pigs, enterotypes have been associated with age ( Lu et al, 2018 ; Le Sciellour et al, 2019 ), sex ( Le Sciellour et al, 2019 ), diets (before and after weaning; Ke et al, 2019 ), and breeds ( Ma et al, 2022 ). In the present study, two enterotypes were identified in 892 fecal samples from 446 pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Enterotyping, firstly described in microbiome research with humans ( Arumugam et al, 2011 ) and later applied to pig studies ( Mach et al, 2015 ; Ramayo-Caldas et al, 2016 ; Lu et al, 2018 ; Yang et al, 2018 ; Ke et al, 2019 ; Le Sciellour et al, 2019 ; Ma et al, 2022 ), involves clustering to decrease the complexity of the fecal microbiota ( Costea et al, 2018 ). Enterotype-like clusters are defined as groups of samples sharing similar bacterial composition ( Arumugam et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Severe gut microbiota imbalance is likely to bring about a series of clinical symptoms such as inflammatory bowel disease and antibiotic related diarrhea. 26,27 A large number of beneficial bacteria become extinct, whereas specific harmful bacteria will take the opportunity to reproduce, then inducing double infections, which may cause serious adverse consequences. 28 Studies have unveiled that prebiotics can promote the proliferation of intestinal probiotics and regulate the structure of the gut microbiota disturbed by antibiotics.…”
Section: Introductionmentioning
confidence: 99%